2017
DOI: 10.1556/018.68.2017.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Linalool-induced oxidative stress processes in the human pathogen Candida albicans

Abstract: The present study investigated the linalool (Lol)-induced effects in acute toxicity tests in the human pathogen Candida albicans (C. albicans). Lol treatments induced reduced germ tube formation of the pathogen, which plays a crucial role in the virulence. In comparison with the untreated control, the exposure of 107 cells ml to 0.7 mM or 1.4 mM Lol for one hour induced 20% and 30% decrements, respectively, in the colony-forming ability. At the same time, these treatments caused dose-dependent decrease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Numerous studies have reported the antiseptic activity of L. angustifolia flower essential oil [29,38,44,[49][50][51][52][53]. It is effective against Gram-positive bacteria (Staphylococcus aureus, Enterococcus faecalis, Listeria monocytogenes, and Bacillus subtilis) and Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa, Salmonella enteritidis, Klebsiella pneumoniae, and Vibrio fluvialis), as well as yeasts and filamentous fungi (Candida albicans, Aspergillus niger, and Penicillium expansum), with the essential oil being much more effective against yeasts than against bacteria [29,38,44,53]. Since the chemical composition of L. angustifolia essential oils varies according to the place of harvest, the antimicrobial activity also varies [29].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported the antiseptic activity of L. angustifolia flower essential oil [29,38,44,[49][50][51][52][53]. It is effective against Gram-positive bacteria (Staphylococcus aureus, Enterococcus faecalis, Listeria monocytogenes, and Bacillus subtilis) and Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa, Salmonella enteritidis, Klebsiella pneumoniae, and Vibrio fluvialis), as well as yeasts and filamentous fungi (Candida albicans, Aspergillus niger, and Penicillium expansum), with the essential oil being much more effective against yeasts than against bacteria [29,38,44,53]. Since the chemical composition of L. angustifolia essential oils varies according to the place of harvest, the antimicrobial activity also varies [29].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Germ tube formation initiates the switch to the more phagocytosis-resistant hyphal form, creating an intense pressure that allows tissue penetration [52]. Lavender oil seems to inhibit germ tube formation by inducing stress through reactive oxygen species (ROS) generation and, thus, reduces the spreading of the fungus in the host tissues [52,53]. Furthermore, linalool has been reported to inhibit the expression of HMG-CoA reductase in fungi, thus preventing ergosterol biosynthesis, leading to fungal cell death [53].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Recently, LIN was found to exhibit antifungal activity by arresting the C. albicans cell cycle. In addition, it induces a reduction in cell size and abnormal germination and inhibition of C. albicans germ tube formation (which plays an important role in the virulence) [1,55,56]. LIN also displays anticandidal activity toward the cells in biofilms [1,51].…”
Section: Mode Of Antifungal Action Of Linmentioning
confidence: 99%
“…In addition to the action on bacterial pathogens, linalool also exhibits antifungal properties, both against yeast-like fungi, e.g., C. albicans [ 66 ], and dermatophytes, e.g., Trichophyton rubrum . De Oliveira Lima et al [ 67 ] demonstrated a positive effect (MIC = 256–512 µg/mL) of linalool on T. rubrum strain resistant to fluconazole, commonly used in the treatment of dermatophytosis.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…It oversees the conversion of HMG-CoA to mevalonic acid. Mate et al [ 66 ] showed that linalool directly influences the composition of the fungal plasma membrane by inhibiting the expression of HMG-CoA reductase. Moreover, these authors proved that linalool induces changes in the fatty acid composition in the fungal cell by increasing the level of polyunsaturated and unsaturated fatty acids.…”
Section: Antimicrobial Activitymentioning
confidence: 99%